DOES LEGAL TRANSPLANTATION WORK? THE CASE OF INDONESIAN CORPORATE GOVERNANCE REFORMS - Harijono Harijono; George Tanewski (Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
This study examines the impact of corporate governance reforms by analysing the relation between firms’ operating performance and key ownership structure and corporategovernance variables on a sample of firms listed on the Jakarta Stock Exchange between the periods 1993 to 2007. Contrary to widespread belief that reforms in Indonesia havefailed, this paper provides empirical evidence in support of the positive impact of corporate governance reforms. While the impact of family control, the firms’ business group affiliation, divergence between cash flow and control rights and political connection are all negatively associated with firms’ operating performance (ROA) for the pre-reformperiod (i.e., 1993-1999), these negative effects disappear during the post-reform period (i.e., 2001-2007), except for family control. More importantly, the relationship betweenfamily control and operating performance is negative only when the family’s control right exceeds their cash flow right. This study provides some empirical evidence and insights toboth regulators and development assistance agencies on the effectiveness of Indonesian corporate governance reforms.Keywords: corporate governance reform, controlling shareholders, firm performance, Indonesia